The Orthopedic Effects of Electronic Cigarettes: A Systematic Review and Pediatric Case Series - Maxwell Luke Armstrong; Nicholas Smith; Rhiannon Tracey; Heather Jackman (MDPI AG, 2022)
Electronic cigarette (EC) use is highly prevalent, especially in the adolescent population, where 29% of Canadian adolescents have used an EC in the past thirty days per national surveys. Our pediatric orthopedic referral centre observed a cluster of delayed unions of bone fractures in adolescents using ECs and present the case series here. We then asked whether electronic cigarettes impair bone healing or influence orthopedic outcomes. A PRISMA-compliant systematic review was carried out, which revealed no human clinical studies and a general paucity of evidence around ECs and musculoskeletal health. The existing experimental evidence relevant to orthopedics is summarized. The effect of ECs on the musculoskeletal system is poorly understood and is a target for further research.